Accounting Career Choice Theories: Is Culture an Impediment? - Rkein, Ali; Rkein, Hassan Ibrahim (Archives of Business Research, 2018)
At a time where an enormous amount of resources have been allocated and spent towards achieving a promising future for all Australians including aboriginal and Torres Strait Islander people. And In a period of increasing awareness among Indigenous Australians that accounting specialization is important and greatly needed for self-determination, the inferior representation of Indigenous Australians majoring in accounting requires attention to understand the reasons behind the dearth of Indigenous accountants that exist in the profession. This paper, while drawing on career choice theories, builds on the Yin/Yang principles of societal values of life, developed by Hines (1992), to explain the cultural constructs of developing an intention to major or not in accounting. The paper tries to identify the impediments preventing Indigenous students from majoring in accounting, by understanding the Yin-based Indigenous cultural identity and relating it to the Yang- infused accounting values.